Using cost-benefit analysis to understand adoption of winter cover cropping in California's specialty crop systems - DeVincentis, Alyssa J.; Solis, Samuel Sandoval; Bruno, Ellen M.; Leavitt, Amber; Gomes, Anna; Rice, Sloane; Zaccaria, Daniele (Journal of Environmental Management, 2020)
Winter cover crops could contribute to more sustainable agricultural production and increase resiliency to climate change; however, their adoption remains low in California. This paper seeks to understand barriers to winter cover crop adoption by monetizing their long-term economic and agronomic impacts on farm profitability in two of California's specialty crop systems: processing tomatoes and almonds. Our modeling effort provides a present, discounted valuation of the long-term use of winter cover crops through a cost-benefit analysis. A net present value model estimates the cumulative economic value of this practice. We then explore how the long-term trade-offs associated with winter cover crops can affect an operation's profits under a spectrum of hypothetical changes in California's agricultural landscape. Our analysis sheds light on the barriers to adoption by reporting benefit-cost ratios that indicate profitability across several scenarios; however, benefits and costs accrue differently over time and with long planning horizons. At the same time, a small portion of gained benefits are external to the grower. Findings from this study reveal that winter cover crops in California can be profitable in the long-term, but the extent of profit depends on the cropping system, extent of irrigation savings due to improved soil function, access to financial subsidies and climate change. Winter cover crops can return positive net benefits to growers who have flexible contractual obligations, can wait for the long-term return on investment and manage cover crops as closely as cash crops. This analysis contributes to the study of conservation agriculture practices by explaining possible reasons for low adoption through an economic valuation of the implications of soil management choices and policy counterfactuals.